Engaging students through social media : evidence based practices for use in student affairs - Junco, Reynol (Jossey-Bass, 2014)
"Using social media to enhance learning outcomes, engagement, and retentionAlthough research shows that most of today's college students adopt and use social media at high rates, many higher education professionals are unaware of how these technologies can be used for academic benefit. Author Reynol Junco, associate professor at Purdue University and fellow at the Harvard Berkman Center for Internet & Society, has been widely cited for his research on the impact of social technology on students. In Engaging Students through Social Media: Evidence-Based Practice for Use in Student Affairs, he offers a practical plan for implementing effective social media strategies within higher education settings. The book bridges the gap between a desire to use social media and the process knowledge needed to actually implement and assess effective social media interventions, providing a research-based understanding of how students use social media and the ways it can be used to enhance student learning. Discover how social media can be used to enhance student development and improves academic outcomes Learn appropriate strategies for social media use and how they contribute to student success in both formal and informal learning settings Dispel popular myths about how social media use affects students Learn to use social media as a way to engage students, teach online civil discourse, and support student development The benefits of social media engagement include improvements in critical thinking skills, content knowledge, diversity appreciation, interpersonal skills, leadership skills, community engagement, and student persistence. This resource helps higher education professionals understand the value of using social media, and offers research-based strategies for implementing it effectively"--